2017
DOI: 10.1016/j.heliyon.2017.e00394
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antileishmanial activity of Mexican medicinal plants

Abstract: Aim of the studyTo evaluate the anti-leishmanial activity and cytotoxicity of aqueous and organic extracts of ten plants used in Mexican traditional medicine as anti-parasitics.Materials and methodsFor the organic extracts, plant material was macerated in dichloromethane (CH2Cl2) and dichloromethane/methanol (CH2Cl2/MeOH) (1:1) during two weeks; the aqueous extracts were prepared by infusion. The extracts were tested against promastigotes and intracellular amastigotes of Leishmania amazonensis. The cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 36 publications
1
19
0
3
Order By: Relevance
“…They are safe, cheaper and partly available in endemic countries. [22][23][24][25] Therefore, the research on the antileishmanial effects of medicinal plants is urgently essential. In this study, the antileishmanial effects of the ethanolic extracts of Ixora brachiata root on L. major and L. infantum promastigotes were evaluated by MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…They are safe, cheaper and partly available in endemic countries. [22][23][24][25] Therefore, the research on the antileishmanial effects of medicinal plants is urgently essential. In this study, the antileishmanial effects of the ethanolic extracts of Ixora brachiata root on L. major and L. infantum promastigotes were evaluated by MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, various compounds derived from plants have showed a leading role and ability as a source of specialized metabolites with medical effects as well as pharmacological activities. In addition, it was reported that various extracts/compounds derived from plants and synthetic compounds could be used in the medical field as useful resources for treating acute or chronic infectious diseases caused by schistosomiasis, leishmania, malaria, or tuberculosis, as well as viral diseases including middle east respiratory syndrome (MERS) or Zika fever and avian influenza [16,17,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The results derived from that evaluation showed that the dichloromethane extract prepared from the aerial parts of a pink-yellow cultivar of L. camara var. aculeata (L.) collected in central Mexico displayed significant activity against L. amazonensis promastigotes and amastigotes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%